Enhancing Brain Tumor MRI Classification Performance Using EfficientNetV2-B3 with an Efficient Channel Attention Module - Navira Rahma Salsabila; Lailil Muflikhah; Edita Rosana Widasari (Faculty of Computer Science (FILKOM) Brawijaya University, 2025)
Early identification of brain tumors using magnetic resonance imaging helps doctors make quick and informed decisions about treatment. Although recent deep learning approaches achieve high accuracy, many rely on complex architectures that increase computational cost and limit interpretability. In order to overcome these constraints, this work proposes a system for four-class brain tumor classification utilizing a public MRI dataset of 3,264 images that is built on EfficientNetV2-B3 and an Efficient Channel Attention (ECA) module used after feature extraction and Grad-CAM. The ECA module enhances cross-channel feature representation with minimal computational overhead. Experimental results indicate consistent performance gains over the baseline model, with accuracy increasing from 97.58% to 99.09% and macro-averaged F1-score from 97.51% to 99.08%. Despite the strong baseline, these gains are achieved without increasing architectural complexity. Grad-CAM visualizations support model interpretability by highlighting tumor-relevant regions that contribute most to the classification decisions. Overall, the proposed framework provides a balanced trade-off between classification accuracy, computational efficiency, and interpretability within the evaluated setting.